Mora Insertion in Tetsǫ́t’ıné: apparent cases of under- and overapplication - Jaker, Alessandro Michelangelo (Proceedings of the Annual Meetings on Phonology, 2023)
Tetsǫ́t’ıné is a dialect of Dëne Sųłıné (ISO: CHP) spoken in Canada’s Northwest Territories. In Tetsǫ́t’ıné, prefix vowel length is subject to a complex set of conditions. The basic generalization is that when a consonant is deleted at the same level that a preceding prefix is added, a short vowel results; whereas when a prefix is added first, and an intervocalic consonant deletes at a later level, a long vowel results (Jaker 2022). This paper addresses two apparent counterexamples to this generalation—that is, cases of exceptional long and short vowels, which may be thought of as overapplication or underapplication of mora insertion. In optative paradigms, the consonant ɣ lenites to w in the singular forms at Level 3. w then deletes at Levels 4 and 5, resulting in a short vowel following Level 4 and 5 prefixes. Conversely, the prefixes θe and ɲe are preceded by a null vowel lexically pre-associated to a High tone. This null vowel acquires a mora at Level 2, thus resulting in an exceptionally long vowel when the initial consonants of θe and ɲe are deleted following a Level 4 prefix.